Indicadores de desempenho em usinas de cana-de-açúcar: uma proposta de modelo - Pavani, Daniel Augusto Borges (2019)
Agribusiness is fundamental to the Brazilian economy. One of the sectors that stands out in the Brazilian agribusiness is the sugar-energy. The use of performance indicators, developed from the performance measurement systems found in the literature, are commonly used in decision making in companies in the most diverse sectors. However, many of these indicators do not fully meet corporate goals or are poorly used in decision making. Aiming to contribute to the reduction of this problem, this work aims to elaborate and propose a set of strategic and tactical performance indicators for a sugar and ethanol mill. This set of indicators has the characteristic of covering all areas of the plant to allow decision makers a global and systemic view of the company. The proposed indicators used the logic of the Performance Prism framework for its construction. The indicators were obtained through an action research that involved managers from all areas of the plant. The main contribution of this research is the proposal of indicators that comprise the set of activities (agricultural and industrial) of a sugarcane mill. The proposed model assumes, therefore, that performance indicators of a sugar-alcohol plant should include aspects related not only to the industrialization of sugarcane but also the activities of agricultural production of this raw material. We have proposed indicators not described in the literature that will be used by the company.